Antimicrobial and Antioxidant Activity of Secondary Metabolites Isolated from Citrullus colocynthis (L.) Schrad.: Antimicrobial and antioxidant activity of isolated phytochemicals - Mubsher Mazher; Muhammad Ishtiaq; Muhammad Waqas; Mussaddaq Mazher (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Available antibiotics have lost their efficiency against several multidrug-resistant (MDR) microbes. Phytochemicals possess great antimicrobial activity and can be an alternative to available antibiotics for MDR microbes. Citrullus colocynthis (L.) Schrad is reported as an antimicrobial and anticancer herb in traditional medicinal cultures. Column chromatography was used to isolate secondary metabolites from ethanolic extracts of C. colocynthis whole fruits. Agar well diffusion method was used to determine antimicrobial activity. Antioxidant activity was measured by the DPPH (1,1-Diphenyl-2-Picrylhydrazine) radical scavenging assay. In this research, the informant consensus factor (ICF) and fidelity level (FL) were calculated on the basis of data collected from local herbalists and elderly villagers of age groups 51–60 who had knowledge of ethnomedicinal uses of plants. It was found that mostly the fruit and its parts (rind, pulp, and seeds) of C. colocynthis were used for the treatment of cancer and microbial infections. Alkaloids showed significant antibacterial activity against Micrococcus luteus (activity index 1.11; zone of inhibition (29.1±0.3 mm) and Pseudomonas pickettii (activity index 1.14; zone of inhibition 32.4±1.7 mm) as compared to streptomycin. It was noticed that flavonoids and phenolics at a concentration of 2000 µLmL-1 showed significant inhibition of free radicals, i.e., 91.57 % and 92.31 %, respectively. It was slightly higher than that of standard butylated hydroxytoluene (BHT), which was 89.07 %. It was found that with the increase in the concentration of phytochemicals, their radical scavenging potential also increased. It can be concluded that alkaloids are the main antimicrobial agents. Flavonoids and phenolics have great potential for free radical scavenging.